Cultural heritage, artistic innovation, and activism on Amazigh Berber websites. Issue 1 (2nd January 2020) - Merolla, Daniela
ABSTRACT: New means of communication and networking have intensified the contact among the Amazigh (Berber) communities in North Africa and diasporic locations, reinforcing pre-existent forms of transnationalism and deterritorialisation. The Internet, however, reinforces local identities as well. This article claims that historical memory and visual and verbal art interact with the social and political discourses on Amazigh/Berber websites, producing local, transregional, and transnational forms of identity. The issue is explored by examining Berber websites' production of 'heritage' and artistic innovation linked to the criticism of national historical constructions and of 'globalising' approaches to the Maghreb. The online reactions to the label 'Arab Spring' and the artistic and political discourses of the online project 'New World Embassy of Azawad' are appraised as examples of interrelating political, artistic and identity dynamics. A second issue concerns the interpretation of Amazigh cultural and political discourse. The question is whether Amazigh websites create contradictory discourses to be interpreted in terms of new 'mythologies' or of 'strategic essentialism'.